The sum of (4x -3)/5 + (2x + 14)/10 is how much greater than x?
The first step to answering this question is to simplify the equation. This means making sure that all terms are reduced. In this case the second term is not reduced. Once that is done, there is already a common denominator. From there you can simply add the two terms then reduce.
((4x-3))/5+ ((2x+14))/10=((4x-3))/5+ (2(x+7))/(2(5))
=(4x-3+x+7)/5= (5x+4)/5= x + 4/5
From the wording of the problem, I believe the constant term is all you need for an answer.